Numerical study of pool boiling heat transfer in a large-scale confined space. (25th May 2017) - Tian, Yongsheng; Zhang, Keyuan; Wang, Naihua; Cui, Zheng; Cheng, Lin
Highlights: A three-dimensional pool boiling coupling model in a confined space is constructed. The dynamic characteristics of nucleate boiling heat transfer are analyzed. The characteristics of nucleate boiling heat transfer rely on the height of the tube. Tube pitch effect is more significant with the height increase. Abstract: The article aims to numerically investigate the heat transfer characteristics of pool boiling on large-scale tube bundles, according to the VOF method. We build a numerical model of single tube in a rectangle confined space to simulate the tube bundles based on the Passive Residual Heat Removal Heat Exchanger, which is applied in nuclear power. The numerical model presents the solid substrate coupled heat transfer between the convection in tube and boiling outside tube. We analyze the dynamic and local characteristic of boiling heat transfer along the tube and the effect of the tube pitch on the heat transfer. Heat transfer characteristics vary along the tube vertical direction. The time-average heat fluxes outside surface increase along the tube. The numerical results are compared with the classical correlation and reliable to predict the pool boiling heat transfer for tubes in the intermediate region of bundle.